Isolation and characterization of monoclonal antibodies directed against the DNA repair enzyme uracil DNA glycosylase from human placenta. - Arenaz, P (1983)
A series of monoclonal antibodies has been prepared against the base excision repair enzyme uracil DNA glycosylase isolated from human placenta. Spleen cells from BALB/c mice immunized with purified human placental uracil DNA glycosylase were fused with either P3X63 Ag8.653 or SP2/0 myeloma cells. Hybridomas producing antibodies directed against the placental glycosylase were identified in an enzyme-linked immunosorbent assay. Each positive hybridoma was cloned twice by limit dilution and tested for anti-glycosylase activity in an enzyme immunoprecipitation assay. Each of the four clones examined in detail precipitated enzyme activity in an immunoprecipitation reaction only in the presence of rabbit anti-mouse IgG as a second antibody. No anti-uracil DNA glycosylase activity was observed in a spontaneous hybridoma used as a control. Each monoclonal antibody immunoprecipitated uracil DNA glycosylases isolated from several human tissues. Partial crossreactivity was observed with rat liver glycosylase and with a hamster enzyme. In contrast, no crossreactivity was observed with yeast or Escherichia coli glycosylase. Glycerol gradient sedimentation analysis demonstrated that one of the antibodies bound to the glycosylase at a site that did not diminish its catalytic activity. A second monoclonal antibody bound at a determinant that affected catalytic activity. Analysis of antibody-glycosylase interactions suggests that human cells contain antigenically distinct glycosylase species that may be encoded by individual uracil DNA glycosylase genes. The potential use of these monoclonal antibodies in studies examining the regulation of glycosylase isoenzymes during cell proliferation in normal human cells and in cells from cancer-prone individuals is considered.